2011
DOI: 10.1002/jemt.21095
|View full text |Cite
|
Sign up to set email alerts
|

Azadirachta indica exhibits chemopreventive action against hepatic cancer: Studies on associated histopathological and ultrastructural changes

Abstract: The present study was designed to evaluate the anticarcinogenic potential of Azadirachta indica against N-nitrosodiethylamine (NDEA)-induced hepatocarcinogenesis. Further, the associated histopathological and ultrastructural changes were also analyzed. Hepatic cancer model was developed by the intraperitoneal administration of NDEA to mice at weekly intervals, in successive increasing doses, for a period of 8 weeks. Aqueous A. indica leaf extract (AAILE) was administered orally at a dosage of 100 μg/g body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 29 publications
(23 reference statements)
2
11
0
Order By: Relevance
“…The reduction in food intake and, consequently, the reduction in body weight observed in NDEA‐treated mice could be an indirect indication of the deteriorating hepatic function following exposure to carcinogen (NDEA). Several studies have shown similar reduction in the body weight of animals following the administration of NDEA (Hasegawa et al ., ; Sreepriya and Bali, ; Bharati et al ., ). The increase in hepatosomatic index in the NDEA‐treated group can be correlated to the morphological and histological observations such as increase in size of liver lobes hyperproliferation of cells, and tumour development (Cui et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in food intake and, consequently, the reduction in body weight observed in NDEA‐treated mice could be an indirect indication of the deteriorating hepatic function following exposure to carcinogen (NDEA). Several studies have shown similar reduction in the body weight of animals following the administration of NDEA (Hasegawa et al ., ; Sreepriya and Bali, ; Bharati et al ., ). The increase in hepatosomatic index in the NDEA‐treated group can be correlated to the morphological and histological observations such as increase in size of liver lobes hyperproliferation of cells, and tumour development (Cui et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The control mice received olive oil (vehicle) at 0.1 mL orally thrice a week. The NDEA group received a cumulative dose of 200 mg/kg body weight of NDEA intraperitoneally in 8 weeks as described by Bharati et al ., . LycT was administered orally at a dosage of 5 mg/kg body weight in olive oil thrice a week throughout the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The anticancer action of Azadirachta indica ( A.indica ) against several animal cancer models and cell lines has been established . Studies have pointed out that A. indica affects biotransformation of carcinogens, generation of ROS/RNS, apoptosis, differentiation, proliferation and angiogenesis, which significantly influence the process of tumour formation .…”
Section: Introductionmentioning
confidence: 99%
“…The anticancer action of Azadirachta indica (A.indica) against several animal cancer models and cell lines has been established. [15][16][17][18][19] Studies have pointed out that A. indica affects biotransformation of carcinogens, generation of ROS/RNS, apoptosis, differentiation, proliferation and angiogenesis, which significantly influence the process of tumour formation. [20][21][22] Treatment of colon cancer cell line (HT-29) with a triterpenoid isolated from A. indica caused cell cycle arrest, indicating its ability to affect cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…The existing structural embodiment of our environment and surroundings makes impossible to evade the exposure from its pernicious clutches. Among various pollutants, N-nitrosodiethylamine (NDEA) is a potent environmental carcinogen found in air, soil, water and food [1][2][3] . Metabolic activation of NDEA through hepatic biotransformation enzymes renders liver as a target organ for carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%